Alginate Production from Alternative Carbon Sources and Use of Polymer Based Adsorbent in Heavy Metal Removal - Çiğdem Kıvılcımdan Moral; Merve Yıldız (International Journal of Polymer Science)
Alginate is a biopolymer composed of mannuronic and guluronic acids. It is harvested from marine brown algae; however, alginate can also be synthesized by some bacterial species, namely, Azotobacter and Pseudomonas. Use of pure carbohydrate sources for bacterial alginate production increases its cost and limits the chance of the polymer in the industrial market. In order to reduce the cost of bacterial alginate production, molasses, maltose, and starch were utilized as alternative low cost carbon sources in this study. Results were promising in the case of molasses with the maximum 4.67 g/L of alginate production. Alginates were rich in mannuronic acid during early fermentation independent of the carbon sources while the highest guluronic acid content was obtained as 68% in the case of maltose. The polymer was then combined with clinoptilolite, which is a natural zeolite, to remove copper from a synthetic wastewater. Alginate-clinoptilolite beads were efficiently adsorbed copper up to 131.6 mg Cu2+/g adsorbent at pH 4.5 according to the Langmuir isotherm model.